Association Between Interpersonal Violence With Inadequate Nutritional Status Among Brazilian Adolescents. Issue 13 (July 2022) - Marques, Emanuele Souza; Hasselmann, Maria Helena; de Barros Vianna, Gabriela Vasconcellos; de Paula Mendonça, Eliane; Azeredo, Catarina Machado
Research focusing on the relationship between interpersonal violence and nutritional status in adolescence is scarce and has distinct results. The objective of this study is to investigate the association of family physical and sexual violence with inadequate nutritional status in Brazilian adolescents. We used data from the 2015 Brazilian National Survey of School Health. This study includes 11.850 students, older than 13 years, attending from sixth to ninth grade of elementary school and from the 1st to the 3rd year of high school. The exposures were family physical violence and rape. The outcome was nutritional status, assessed through body mass index. The association between exposures and outcome were investigated using a multinomial logistic regression model. These analyses were adjusted for demographic, socioeconomic, and family variables. The prevalence of family physical violence victimization was approximately 14% among adolescents for both sexes. The prevalence of rape was 4.6% and 5.7% among male and female adolescents, respectively. Family physical violence was not associated with being underweight, overweight, or obese, in either crude or adjusted models for both sexes. Sexual violence was inversely associated with being underweight only for male adolescents (OR: 0.21, CI 95%: 0.06–0.75). In female adolescents, sexual violence was associated with overweight/obesity (OR: 1.64, CI 95%:1.15–2.33). In this study, rape, but not family physical violence victimization, was associated with nutritional status in adolescents of both sexes. Nonetheless, this association was different between boys and girls. Rape was inversely associated with being underweight in male adolescents, whereas, in female adolescents, it was associated with excess body weight.